Corporate governance mechanisms and environmental management system on environmental disclosure - Tauhida, Tihana Tyan Zahrotuddinia; Wahyuningrum, Indah Fajarini Sri (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2025)
This research aims to examine the influence of corporate governance and EMS on environmental disclosure. The corporate governance variable is proxied by managerial ownership, foreign ownership, frequency of board of commissioner meetings, proportion of independent board of directors, and gender diversity. The data in this research is secondary data originating from the annual reports and sustainability reports of property & real estate companies listed on the Indonesia Stock Exchange in 2021-2023. This research uses quantitative research methods with data collection techniques by means of literature research and documentation research, and the results are analyzed by panel data regression analysis techniques. Test result using panel data regression show that the managerial ownership, foreign ownership, and gender diversity does not affect environmental disclosure while frequency of board of commissioner meetings, proportion of independent board of directors, and EMS variable have a significant positive effect on environmental disclosure. test result also show that the control variable profitability proxied by ROA does not influence environmental disclosure. This research contributes by highlighting insight into specific impact of corporate governance components and EMS on environmental disclosure within property & real estate sector. The findings provide a more nuanced understanding of how these components interact to influence corporate transparency regarding environmental issues.